Optimization of Guava Leaf Extract Loading in Chitosan-Based Nanoencapsulation for Oxidation Inhibition - Ernik Dwi Safitri; Ngurah Ayu Ketut Umiati; Agus Subagio (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2026)
Guava leaves contain various active compounds, including tannins, phenolics, and flavonoids, with potential as antioxidants, antimicrobials, and anti-inflammatory agents. Guava leaf extract has been used in various fields, including manufacturing, as a corrosion inhibitor. Nanoencapsulation is a method for maintaining the stability and durability of guava leaf extract under various environmental conditions, including changes in pH and temperature, as well as chemical degradation. In this study, guava leaf extract was obtained by ultrasonication. Nanoencapsulation of guava leaf extract at varying concentrations was performed using the ionic gelation method with the natural polymer chitosan and the cross-linking agent STPP. Sample characteristics were identified using X-ray Fluorescence Spectroscopy, Fourier Transform Infrared Spectroscopy, Particle Size Analysis, and Inductively Coupled Plasma–Optical Emission Spectroscopy. The optimal concentration of guava leaf extract in this encapsulation study, 2000–3500 ppm, resulted in particle sizes of 315–390 nm and a polydispersity index below 0.5, indicating well-dispersed particles. The smaller, more dispersed particles will increase the electrostatic bonding between particles, thereby strengthening the interactions involved in the formation of the complex layer. This layer reduces pyrite oxidation by decreasing the release of sulfur and iron into the leaching environment. Nanoencapsulation of guava leaf extract using the ionic gelation method with chitosan is quite effective.